Proses Sosialisasi dan Keluar Karyawan Perusahaan: Tinjauan pada Fenomena Turnover - Tanjung, Nurjannatin Aliya Albany; Islami, Farina (School of Communication Science and Media Business, 2025)
Turnover is a situation when an employee decides to exit and is no longer involved with the company. The increase in turnover percentage that occurs in Indonesia needs attention because it can have an impact on both the individuals and companies involved. This research seeks to explore this phenomenon by conducting in-depth interviews with two sources with experience of more than three company turnovers uses the theory of socialization process and exit process from Miller, Jablin and Putnam. The results of this research state that success in the socialization process can reduce employee turnover intention, including through collecting in-depth information by relevant individuals, disclosure of information and organizing training or mentoring programs by the company. This can minimize culture shock that occurs, minimize individual expectations of the company and vice versa, build an environment that tends to be comfortable, make it easier for employees and the company to assimilate, and increase employee commitment so that it can reduce employee turnover.